1998
DOI: 10.1051/rnd:19980201
|View full text |Cite
|
Sign up to set email alerts
|

Digestive and metabolic adaptations of ruminants to undernutrition, and consequences on reproduction

Abstract: -In response to undernutrition, short-(days) and medium-term (weeks) adaptations are more pronounced for splanchnic organs than for other tissues. For the latter, the long-term response involves a sequential mobilization (fat > muscle > bone) with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
195
1
37

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 242 publications
(260 citation statements)
references
References 62 publications
27
195
1
37
Order By: Relevance
“…A reduced blood supply to the portal-drained viscera, mainly the rumen and liver, and thus, a decreased metabolic rate of these organs presumably contribute markedly to energy conservation (Chilliard et al, 1998). All cows also lowered physical activity (reduction of movements, shorter standing times) during P2 which is contrary to experimental results showing that steers (Derno et al, 2005) and calves (Schrama et al, 1995) spend more time standing during energy restriction.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…A reduced blood supply to the portal-drained viscera, mainly the rumen and liver, and thus, a decreased metabolic rate of these organs presumably contribute markedly to energy conservation (Chilliard et al, 1998). All cows also lowered physical activity (reduction of movements, shorter standing times) during P2 which is contrary to experimental results showing that steers (Derno et al, 2005) and calves (Schrama et al, 1995) spend more time standing during energy restriction.…”
Section: Discussionmentioning
confidence: 57%
“…Stress-induced hyperthermia is known to be mediated by the dorsomedial hypothalamus and sympathetic premotor neurons in the rostral medullar raphe region that induce thermogenesis and peripheral vasoconstriction (Kataoka et al, 2014) which is in accord with activation of the sympathetic branch of the ANS in pregnant, fasting <L MAX cows. The plasma level of cortisol is influenced by feeding and by the nutritional status (Samuelsson et al, 1996, Chilliard et al, 1998, and has been shown to increase as an anticipatory response to forthcoming food (Willett and Erb, 1972) and in feed-deprived cows (Mills and Jenny, 1979;Samuelsson et al, 1996). Elevated levels of cortisol are important for glucose supply in animals being in NEB (Samuelsson et al, 1996), but a noticeable increase was only seen in lactating >L MAX cows at day 2 (P2 + P3) of the experiment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations